THE USE OF PADLET APPLICATION (PA) TO ENHANCE STUDENTS’ WRITING ABILITY: An Experimental Research - Musdir, Zurtia; St. Asriati AM; Andi Baso, Farisha (Journal of Computer Interaction in Education, 2018)
This research aimed to know the students writing ability after applied Padlet Application on class 11th grade students of MAN 1 Makassar. The research problems of this research does the students writing ability improve using Padlet application and does the students interest in learning English using Padlet application. The method of this research was pre experiment design that consisted of pretest, treatment and posttest. The aimed of this research was to analyze whether or not the used of Padlet Application improved the students’ writing skill and to analyze whether or not the used of Padlet Application made students’ interest in learning English. The researcher used two kinds of test were writing test to measure the improvement of students’ writing skill in terms of content and organization and using questionnaire to measure the interest of students using Padlet application. This questionnaire consisted of five positive statements and five negative statements. Based on the data analysis, it found that the improvement of students’ writing skill in terms of content was 54.70 became 82.35, with the t-test value of content was greater than t-table (16.58>2.11). While the improvement of students’ writing skill in terms of organization shows the result was 57.05 became 87.05 with the t-test value of organization was greater than t-table (34.98>2.11). Based on the result of questionnaire data, it shows that the percentage completely positive and negative statements was 79.11 % as good categorized. It means, the result of writing test and questionnaire data proved that Padlet Application was effective and applicable to improve and interest students’ writing skill at the eleventh grade of MAN 1 Makassar